Ketoasidosis Diabetik pada Anak: Laporan Kasus - Astrellatiffany Kuntjoro; Arnold Soetarso (Cermin Dunia Kedokteran, 2024)
The incidence of diabetic ketoacidosis (DKA) in children with type 1 diabetes mellitus reaches 1–12 per 100 patients each year. The case is a boy aged 13 years 10 months with chief complaints of weakness and drowsiness. Blood sugar levels 532 mg/dL, blood ketone levels 6.6, blood pH 7.13, HbA1c 19.2%. The principles of DKA management include fluid therapy, insulin, electrolyte balance, treat the underlying disease, and monitor complications.